A review of Venezuelan migration to Colombia through memes on social media: revanchism and perverse representations - Córdoba, Juan Carlos (2020)
This article is the result of an investigation that analyzed the incidence of Venezuelan migration in the imaginary that Colombians have of migrants and of themselves, as well as of the current socio-political situation of the two countries, expressed through “memes” that circulate on social networks, which are taken as active scenarios of the political sphere that allow observing the variations in public opinion. Methodologically, the research was framed within the mixed approach (qualitative-quantitative), based on the analysis of the discourse of a set of memes extracted from Facebook and Twitter, whose preliminary results were contrasted with those of surveys and focus groups directed at Colombian citizens to identify types of imaginaries around Venezuelan migration and its impact on the image that Colombians have of their own reality and of the migrant